Penerapan Augmented reality Berbasis Minimax Algorithm pada Game Papan Cerdas - Latius Hermawan; Maria Bellaniar Ismiati (Jurnal Buana Informatika, 2022)
Abstract. Application of Augmented reality Based on Minimax-Alpha Beta Pruning Algorithm on Smart Board Games. Augmented reality technology is growing very rapidly making game production more innovative and attractive. The implementation of this technology also has the potential for traditional board games which are starting to be replaced by computer-based digital games. The method used in the digital board is Minimax which is zero-sum based where one point of the opponent's victory will reduce the player's one point. This method underlies the way of thinking to get critical steps in several types of games being played. Minimax will result in a lower probability of defeat and increase the probability of winning. The results obtained are that Minimax which was developed with Alpha Beta Pruning to make opponents think like humans so that artificial intelligence in it is suitable to be applied. The test results also give a 63% win for the AI (Artificial Intelligence) used, so the game becomes challenging.Keywords: Game, augmented reality, Minimax, Board Abstrak. Teknologi Augmented reality yang berkembang sangat pesat membuat produksi game lebih inovatif dan atraktif. Implementasi teknologi tersebut juga berpotensi untuk permainan papan tradisional yang mulai tergantikan oleh permainan digital berbasis komputer. Metode yang digunakan dalam digital board adalah Minimax yang berbasis zero-sum dimana satu poin kemenangan lawan akan mengurangi satu poin pemain. Metode ini mendasari cara berfikir untuk mendapatkan langkah-langkah kritis dalam beberapa jenis game yang dimainkan. Minimax akan menghasilkan kemungkinan kekalahan yang sedikit dan memperbanyak kemungkinan kemenangan. Hasil yang didapatkan yaitu Minimax yang dikembangkan bersama Alpha Beta Pruning mampu membuat lawan berfikir layaknya manusia sehingga kecerdasan buatan didalamnya cocok untuk diterapkan. Hasil pengujian juga memberikan hasil 63% kemenangan bagi AI (Artificial Intelligence) yang digunakan, sehingga permainan menjadi menantang. Kata Kunci: Game, augmented reality, Minimax, papan